Empathetic technologies: digital materiality and video ethnography. Issue 4 (2nd October 2017) - Pink, Sarah; Sumartojo, Shanti; Lupton, Deborah; Heyes LaBond, Christine
Abstract : In this article, we advance recent theoretical and methodological discussions regarding the use of video techniques for generating empathetic encounters. We do so through a focus on how these techniques might be rendered in research conducted through sites of action and experience that are explicitly constituted through forms of digital materiality, whereby the digital and material are understood as relational and emergent. We argue for a processual view of digital materiality and in correspondence with this, of the research process, whereby empathetic imagining is itself understood as emergent from the research encounter. By way of example we draw on recent video ethnography research that has used GoPro and researcher-held video recording in collaboration with participants, in order to record and develop understandings of their experiences of self-tracking and cycle commuting.